Analisis Implementasi Prinsip Universal Desain dalam Meningkatkan Aksesibilitas bagi Penyandang Disabilitas (Studi Kasus: SMK TI BAZMA Bogor) - Yanuar Eka Putri; Sukawi Sukawi (Jurnal Sipil dan Arsitektur, 2025)
Accessibility for persons with disabilities is a crucial aspect of infrastructure development, especially in educational environments such as school dormitories. SMK TI BAZMA Bogor has dormitory facilities that must ensure easy access for all residents. The objective of this investigate is to look at how universal design principles can be applied to enhance accessibility within the SMK TI BAZMA Bogor dormitory. This investigate employs a quantitative approach with a descriptive method. Information were collected through observation and analysis of facility compliance with Ministerial Regulation PU No. 30 of 2006. The analyzed aspects include parking areas, horizontal circulation, room dimensions, doors, stairs, toilet facilities, furniture, and guiding paths.